KAP ANALYSIS AMONG NURSES WORKING IN A TERTIARY CARE HOSPITAL REGARDING PATIENT SAFETY - ASAD, .; SAMREEN, S; YASMEEN, T; AKHTAR, S; BANO, S (Biological and Clinical Sciences Research Journal, 2024)
Patient safety is a critical aspect of healthcare quality, requiring healthcare professionals, particularly nurses, to possess adequate knowledge, maintain a positive attitude, and adhere to safe practices. This study evaluates the knowledge, attitudes, and practices of nurses regarding patient safety in a tertiary care setting. Objective: To assess the knowledge, attitudes, and practices of nurses regarding patient safety at a tertiary care hospital. Methods: A cross-sectional study was conducted in the Nursing Department of Nishtar Hospital, Multan from October 2023 to October 2024. A total of 100 nurses from all departments with at least one year of working experience and a bachelor’s degree were included in the study. A 42-item questionnaire containing four sections was employed to assess participants. Results: The mean knowledge score was 8.9 ± 1.43 among which 60% had good knowledge and 40% had poor knowledge about patient safety. The mean attitude score was 56.59 ± 10.23 among which 59% had a positive attitude and 41% had a negative attitude. The mean practice score was 5.71 ± 1.65 among which 60% had good practices and 40% had poor practices. Multiple regression analysis showed that knowledge score has no significant predictors. However, age and knowledge of patient safety during education were significantly associated with attitudes. Knowledge of patient safety during education was also significantly associated with practices. Conclusion: The knowledge, attitudes, and practices regarding patient safety were satisfactory in nurses working in tertiary care hospitals. However, improvements are required in hospital culture and policies to enhance patient care.